2012
DOI: 10.1016/j.sjpain.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental pressure-pain assessments: Test-retest reliability, convergence and dimensionality

Abstract: Introduction Experimental pain studies can provide unique insight into the dimensions of pain and into individual differences in pain responsiveness by controlling different aspects of pain-eliciting stimuli and pain measures. In experimental pain studies, pain responsiveness can be assessed as pain threshold, pain tolerance or pain ratings. The test-theoretical qualities of these different measures, however, have not yet been completely documented. In the current study, several of these qualities were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 23 publications
2
71
0
3
Order By: Relevance
“…Pressure pain threshold was measured using a digital pressure algometer (Somedic, Sweden), a device that is recognized as a valid and reliable measure when used by a trained assessor [22,28,33]. Standard method and instructions were used [26].…”
Section: Physical Outcome Measuresmentioning
confidence: 99%
“…Pressure pain threshold was measured using a digital pressure algometer (Somedic, Sweden), a device that is recognized as a valid and reliable measure when used by a trained assessor [22,28,33]. Standard method and instructions were used [26].…”
Section: Physical Outcome Measuresmentioning
confidence: 99%
“…Importantly, TRR places an upper limit on validity. Whereas the TRR of self-reported pain has been extensively examined in clinical measures [12,16,25,36], there are presently no studies of pain neural markers that report information about TRR. In fact, very few studies have even examined TRR related simply to fMRI findings about pain processing.…”
Section: Introductionmentioning
confidence: 99%
“…Although pain threshold and pain tolerance are both considered measures of pain sensitivity, there is evidence that they represent different processes: An earlier study using the same pain assessment methodology showed that pain tolerance is only modestly correlated to pain threshold (r % .40) but moderately related to subjective sensory and affective pain ratings (r % .60) (Lacourt et al, 2012). Pain threshold on the other hand showed low correlations with pain ratings (r % .30).…”
Section: Discussionmentioning
confidence: 99%
“…These algometric pain sensitivity measures showed good testretest reliability for tests repeated within one session (intraclass correlation coefficient (ICC) > .80) (Lacourt et al, 2012;Potter et al, 2006) and over days (ICC > .70) (Potter et al, 2006).…”
Section: Pain Sensitivitymentioning
confidence: 91%
See 1 more Smart Citation